The Effects of Multimedia Assisted Quantum Learning Models Towards Science Learning Outcomes in Elementary School Students (Universitas Negeri Semarang, 2020)
The low student learning outcomes usually due to learning process which have not used a variety of models and emphasizesmemorization learning. Media is used to create interesting learning so that students canbe active in learning activities. The objective of this research was to determine the effect of multimedia-assisted quantum learning models on science learning outcomes in elementary school students. This type of research was a Quasi Experimental with pretest-posttest control group design. The samples of this research were 28 students of grade IV students of SDN Ngesrep 02 and 27 students of grade IV of SDN Ngesrep 03. Instruments used in this researchwere observation sheets and tests. Data analysis techniques include normality test, homogeneity test, n-gain score test and t-test. The results show that the average score of learning outcomes in the experimental class was 76.85 and the control class was 73.39. The independent test results state that there are differences between the experimental class and the control class, indicated by tcount>ttable of the significant value of 0.024 <0.05. It can be concluded that there was a significant influence in learning using multimedia-assisted quantum learning models towards student learning outcomes.